Government, national consensus and economic adjustment - Thomas, Desmond (Institute of Development Studies. Univ. of Guyana TurkeyenGY, 1994)
Emphasizes the role of the government as an intermediary in the context of contending socio-economic interest groups and reflecting the consensus or the dominant direction. Explores the concept of the government as an interacting rather than an autonomous agent. Discusses the implications for policy-making in a period of instability. Pays attention to the Jamaican experience and the challenges posed by high budget deficits. Addresses the issue of commitment to sharing the burden of adjustment, and emphasises the role of government in the stabilisation process.